Schaum's outline of theory and problems of development economics - Salvatore, Dominick; Dowling, Edward Thomas (New York : McGraw-Hill, 1977)
This book defines a systematic way in which theoretical and practical core of development economics will be adopted to solving critical economic problems.
Includes index.
obn 24/01/2019
Loans
Keywords: Economic development; Development economics